Artificial Neural Networks and Wireless Network Technology: A Review of Literature - Abdul Basit; Noor un Nisa (Journal of ICT, Design, Engineering and Technological Science, 2020)
The research paper is an introduction to the artificial neural networks and wireless network by using sensor technology. There are myriads types of neural networks which are used in computer network and wireless network technology. Neural networks explain and give the proper demonstration for the applications of neural networks and wireless network. The artificial network and wireless network have strong connection and can be investigated and explained properly. There are also some models which are called mathematical models which can explain and demonstrate the artificial and wireless networks in detail. There are many organizations which are using artificial neural networks by using sensor technology for wide range of purpose. A new technology ZigBee introduced in artificial networks and wireless networks by evolving the new protocol system based on meter reading. Artificial neural networks and wireless network along database management system have great importance in revolutionizing the world in artificial and wireless technology by using different wireless sensors, RF chip, and fusion of RFID system along with nodes of ZigBee technology.